A survey of strategies for communication networks to protect against large-scale natural disasters - Gomes, Teresa (2018)
Abstract—Recent natural disasters have revealed that emer- gency networks presently cannot disseminate the necessary dis- aster information, making it difficult to deploy and coordinate relief operations. These disasters have reinforced the knowledge that telecommunication networks constitute a critical infrastruc- ture of our society, and the urgency in establishing protection mechanisms against disaster-based disruptions. Hence, it is important to have emergency networks able to maintain sustainable communication in disaster areas. Moreover, the network architecture should be designed so that network connectivity is maintained among nodes outside of the impacted area, while ensuring that services for costumers not in the affected area suffer minimal impact. As a first step towards achieving disaster resilience, the RE- CODIS project was formed, and its Working Group 1 members conducted a comprehensive literature survey on “strategies for communication networks to protect against large-scale natural disasters,” which is summarized in this article.